PERANAN PROGRAM PENGEMBANGAN SUMBER DAYA MANUSIA DALAM MENINGKATKAN KINERJA MANDOR PANEN DI PERUSAHAAN PERKEBUNAN KELAPA SAWIT, KABUPATEN BERAU, KALIMANTAN TIMUR - Dahlia; Rusli Anwar; Rusmini; Fadli Mulyadi; Sri Ngapiyatun (Politeknik Pertanian Negeri Samarinda, 2019)
The Role of human resource development program on improving performance of harvesting foremans on oil palm plantation company, berau regency, east kalimantan the background of this study is because the performance of harvesting foremans on oil palm plantation hasn't been maximized notably on the influence of training and awarding their performance. This study aims to determine how far the training and awarding that has been given by the company to harvesting foremans then can affect their perception about training and awarding also to evaluates their performance. This study also exoplores about the characteristic of the harvesting foreman as object of this study. This study used quantitative method which is multiregression analysis with training (x1) and awarding (x2) as independent variables and performance (y) as dependent variable. this study used all the popullation and questioner to collect the data then processed by using SPSS program then comparing the result of the SPSS output with the field conditions.Based on the multiregression analysis result showed that there was an influence between the training and awarding on harvesting foreman' performance with a strong correlation, therefore it could be concluded that the human resource development programs toward harvesting foremans influenced their performance.